Active phase of cobalt oxide (Co3O4) as a promising catalyst for graphene growth by alcohol catalytic chemical vapor deposition - Mohd Abid, Mohd Asyadi 'Azam; Zulkapli, Nor Najihah; Mohd Suan, Mohd Shahadan; Mohamad, Noraiham; Omar, Ghazali (Blue Eyes Intelligence Engineering & Sciences Publication (BEIESP), 2020)
The presence of active catalyst during graphene growth by alcohol catalytic chemical vapour deposition is a compulsory. This study is aimed to validate the effect of annealing temperature for the formation of active cobalt oxide (Co3O4) film on the graphene growth by alcohol catalytic chemical vapour deposition technique. Active Co3O4 film was prepared on silicon wafers by sol-gel process, using cobalt acetate tetrahydrate as the precursor compound and absolute ethanol as the solvent. Them active Co3O4 phase was achieved by annealing process at 450, 500, 550 and 600 °C. The graphene is grown from active Co3O4 film under 900 °C of chemical vapor deposition (CVD) processing temperature for 5 minutes. The obtained Co3O4 was characterized by x-ray diffraction and Raman spectroscopy. The as-grown graphene from active Co3O4 film annealed at 450 ⁰C was characterized by Raman spectroscopy and field emission scanning electron microscope (FESEM). The results demonstrate that spinel type cubic structure of Co3O4 could be produced at the varied annealing temperatures but the optimum XRD result was at 500 ⁰C annealing temperature. The presence of active Co3O4 phase was supported with the exhibited peaks of four Raman-active phonon modes in the Raman spectra. The quality of as-grown graphene determined from the ratio of 2D-band over G-band intensities is 1.010; an indication of few layers of graphene. Active Co3O4 film is able to produce good quality of graphene comparable with Ni and Cu catalysts. And graphene can be used in many devices, including electronic device, energy storage device, power device, and others.